Production of phenolic compounds from in vitro shoots of sugarcane (Saccharum spp.) in temporary immersion bioreactors - Bernal Villegas, Aydiloide (2024)
An alternative way to obtain molecules of high-value from plant origin for the agricultural and pharmaceutical industries is via the production of secondary metabolites from in vitro systems. Among these molecules are phenolic compounds that are important in plant defense system against biotic and abiotic factors. The objective of this work was to establish the culture conditions for the production and scaling up of phenolic compounds from sugarcane shoots produced in Temporary Immersion Bioreactors (TIBs). Two different sucrose concentrations and three inoculum densities of shoots per flask were tested for two sugarcane cultivars C86-56 and C1015-73. These cultivars were micropropagated in TIBs without ascorbic acid for phenolic compound production during 25 days, and were measured every five days. The best established conditions were evaluated on a pilot scale with ten TIBs for three sugarcane cultivars (C86-56, C1051-73 and C87-51). Although phenolic compounds were produced under all conditions evaluated at the experimental level, the most important production was achieved by using 15 shoots per vessel with 20 g.L-1 of sucrose in the absence of ascorbic acid after 25 days of culture. Cultivar C1051-73 had a higher multiplication coefficient independently of the treatments; this effect was not only significant for the phenolic compound production, but also for biomass increases. With respect to the pilot experiment, significant differences were detected for phenolic compound production among the three cultivars with C1051-73 showing the highest yield (23.05 mg.L-1). The results revealed that TIBs are a useful method to produce phenolic compounds with optimum yields.